L Teachers’ Uses, Attitudes, Beliefs, Roles, And Pedagogical Methods About Pronunciation Power Software In English Pronunciation Instruction - Gilakjani, Abbas Pourhosein (2015)
Perisian Pronunciation Power ialah satu perisian teknologi komputer dalam pengajaran sebutan dalam bahasa Inggeris.